Pendaftaran Merek Sebagai Upaya Perlindungan Hukum Produk Usaha Mikro Kecil Menengah Di Kabupaten Karawang - Detya Anggraeni (Universitas Kapuas, 2024)
The growth of Micro, Small, and Medium Enterprises (UMKM) in Indonesia is increasing every year and occupies a strategic position in the national economic structure. One very crucial aspect for all businessman in UMKM is the protection of the intellectual property of their products, such as brands, patents, copyrights, and industrial designs. Unfortunately, awareness of businessman in UMKM is still relatively low in their efforts to protect the intellectual property of their businesses, which in reality can be a valuable asset. So, legal protection is needed to obtain legal certainty for the community. This research aims to reveal legal protection efforts for brands in Indonesia and the role of the Karawang Regency Government in accommodating brand registration for UMKM products. This research uses sociological juridical research or field legal research whose focus is to evaluate applicable legal regulations and the realities that occur in society. The results of the research show that the government makes it easy for businessman UMKM in industry to register brands, namely through a policy of cheaper UMKM brand registration fees, a collaboration between the Director General of IP, Ministry of Law and Human Rights, and the Ministry of Cooperatives and UMKM, as well as registering collective brands for the UMKM industry. The role of the Regional Government, in this case, the Karawang Regency UMKM and Trade Cooperatives Service, in accommodating brand registration for small businesses is to act as a facilitator and catalyst.